2021
DOI: 10.1097/inf.0000000000003178
|View full text |Cite
|
Sign up to set email alerts
|

Blastomycosis in 64 Wisconsin Children: Unanticipated Infection Risk and Severity in Urban Residents

Abstract: Background: Blastomycosis, an endemic mycosis of immunocompetent individuals, is typically seen after exposure to waterways within rural wooded regions. It is not considered a disease of urban environments. Infection can be solely pneumonic or disseminate to skin, bone or central nervous system. Unknown factors influence disease acquisition and severity in children. Methods: We analyzed acquisition risks and disease characteristics of blastomycosis in children seen at a tertiary care center from 1998 to 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Certain racial groups—including African Americans, Native Americans, Asians of Hmong ancestry, and the Indigenous Canadian population—have an increased incidence and severity of disseminated fungal infections 2,5 . Recent studies have suggested that genetic differences in innate immunity among certain ancestral backgrounds may explain this increased susceptibility to fungal infections 6 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Certain racial groups—including African Americans, Native Americans, Asians of Hmong ancestry, and the Indigenous Canadian population—have an increased incidence and severity of disseminated fungal infections 2,5 . Recent studies have suggested that genetic differences in innate immunity among certain ancestral backgrounds may explain this increased susceptibility to fungal infections 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of disseminated blastomycosis vary widely and include asymptomatic infection (up to 50% of cases), pneumonia (53%–75% of cases), disseminated disease involving any organ (25%–40% of cases), or death 1,3,5 . Disseminated blastomycosis can occur in immunocompetent or immunocompromised individuals, while disseminated histoplasmosis is typically an opportunistic infection 2,4 . The skin is the most common extrapulmonary organ system affected, with about 60% of disseminated infections having cutaneous lesions 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations